Introducing Competency-Based Education Based on the Roles that Physiotherapists Fulfil - Dirk Vissers; Ulrike Van Daele; Willem de Hertogh; An de Meulenaere; Joke Denekens (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Introduction: Although there has been a shift towards competency-based medical education in the past decade, littlel iterature is available about the specific use of competency-based   education in physiotherapy education. The purpose of this article is firstly to describe the development of a competency-based educational program for physiotherapy and secondly to present the results of the evaluation of the competency-based program by an independent panel of stakeholders.  Method: A role-based competency framework was gradually developed and implemented in a 5-year university-based physiotherapy education program leading to a Master of Science degree. A stakeholder panel was asked to which degree they agreed that the specified roles and competencies were important for physiotherapists.  Results: Competencies were defined for the roles of clinician, scientist and professional and linked to behavioural indicators, carefully checking that the model covered all Dublin descriptors. Although a vast majority of the stakeholder panel considered the proposed roles (92,8%) and competencies (100%) as a strong characteristic of the program, scientific competencies were generally considered less important than clinical or professional competencies.  Conclusions: Competencies of a role-based educational program for physiotherapy should be aligned with competencies expected in the professional field paying special attention to scientific competencies needed for evidence-based clinical practise and innovation of physiotherapy.